2018
DOI: 10.1055/s-0038-1626715
|View full text |Cite
|
Sign up to set email alerts
|

The Utility of Repeat Midtrimester Anatomy Ultrasound for Anomaly Detection

Abstract: Over 90% of anomalies are detected on the initial fetal anatomic survey. The incremental diagnostic yield then decreases, requiring appreciably more repeat scans to detect one anomaly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 13 publications
1
5
0
Order By: Relevance
“…Regarding the success rate of obtaining optimal 20 + 2 ISUOG planes between pregnant women with a GA ≥ 20 weeks and GA < 20 weeks, we found that those with a GA ≥ 20 weeks had a 1.2 times higher success rate for foetal US screening than women with a GA < 20 weeks. This is similar to previous studies, which found that a lower GA decreases the success rate of achieving optimal visualization [ 11 13 ]. We postulated that the smaller foetus and relatively smaller foetal size to amniotic fluid ratio may affect the possibility of achieving success, and hence the success rate.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Regarding the success rate of obtaining optimal 20 + 2 ISUOG planes between pregnant women with a GA ≥ 20 weeks and GA < 20 weeks, we found that those with a GA ≥ 20 weeks had a 1.2 times higher success rate for foetal US screening than women with a GA < 20 weeks. This is similar to previous studies, which found that a lower GA decreases the success rate of achieving optimal visualization [ 11 13 ]. We postulated that the smaller foetus and relatively smaller foetal size to amniotic fluid ratio may affect the possibility of achieving success, and hence the success rate.…”
Section: Discussionsupporting
confidence: 92%
“…This finding is different from a previous study, which reported that foetal position, oligohydramnios, prior abdominal surgery, and maternal obesity may account for suboptimal US visualization. We hypothesized that our different result may be caused by the definition of each variable, number of sample size calculation which based on GA only and small proportion of some maternal characters such as presence of myoma, obese or abdominal scar, etc [ 11 , 14 16 ]. The most common suboptimal planes in our study were the facial profile and thoracic planes.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a study analyzing the utility of repeat ultrasounds for anomaly detection suggested the yield of repeat ultrasounds may be low, with over 90% of anomalies detected on initial surveys and appreciably more scans required for detection of remaining anomalies. 22 Yet, in our cohort, of the total anomalous fetuses identified, 38.0% were noted in a follow-up ultrasound after the first was suboptimal or incomplete. As one in five individuals with an identified anomaly went on to terminate their pregnancy, we support repeating ultrasounds in an attempt to work toward complete views.…”
Section: Discussionmentioning
confidence: 61%
“…Based on a prior study where an initial ultrasound was incomplete in 14% of individuals at a median gestational age of 18.5-week gestation, 22 a power calculation for a two-sided unpaired t -test determined we would need 826 patients per group to exclude a clinically meaningful difference of more than 5% in incomplete views comparing greater than 20-week gestation to less than 20-week gestation.…”
Section: Methodsmentioning
confidence: 99%
“…First Author: S. Lindsay Wood, MD, University of Alabama, Birmingham, AL Wood and colleagues examined the utility of repeated ultrasound examinations to identify anomalies following an incomplete anatomic survey. 1 In this retrospective cohort study of 13,740 patients, 11,828 (86%) women had the fetal anatomic survey completed on the first attempt, 1,796 (13%) on the second attempt, and 116 (1%) had a third attempt. Overall, 324 (2.4%) anomalies were detected.…”
Section: Featured Manuscripts the Utility Of Repeat Midtrimester Anatmentioning
confidence: 92%